DNA-barcoding identification of Dothistroma septosporum on Pinus contorta var. latifolia, P. banksiana and their hybrid in northern Alberta, Canada. Issue 3 (4th May 2021) - Feau, Nicolas; Ramsfield, Tod D.; Myrholm, Colin L.; Tomm, Bradley; Cerezke, Herb F.; Benowicz, Andy; Samis, Erica; Romano, Ashley; Dale, Angela L.; Capron, Arnaud; Heinzelmann, Renate; Hamelin, Richard C.
Abstract: The ascomycete fungi Dothistroma septosporum (Dorogin) M. Morelet and D. pini Hulbary are both responsible for Dothistroma needle blight disease (DNB) on pines. Using a DNA-barcoding approach, we confirmed that the DNB infection of lodgepole pine ( Pinus contorta Dougl. var. latifolia Engelm.), jack pine ( P. banksiana Lamb.) and their hybrid in four research sites in northern Alberta (Canada) was caused by D. septosporum, confirming that the range of D. septosporum extends east of the Rocky Mountains into Alberta. Analysis of mating-type (MAT) genes showed the presence of both mating types in each of the pine plantations, indicating that the pathogen has the potential to complete its lifecycle in this region. Controlled inoculation confirmed that the two native pines found in this area ( P. contorta var. latifolia and P. banksiana ) and their hybrid are susceptible to D. septosporum, suggesting that continuous monitoring of the disease needs to be carried out to prevent any future outbreak in natural stands.